Job motivation among researchers in Malaysian Institute for Nuclear Technology Research (MINT) - Ab. Wahab, Rohana (1997)
The purpose of the study was to determine the level of job motivation among researchers in the Malaysian Institute for Nuclear Technology Research (MINT) using the framework of Herzberg's Two-Factor Theory. The specific objectives were to determine: (a) the extrinsic motivation of researchers using variables in the hygiene factor, and (b) the intrinsic motivation of researchers using variables in the motivator factor. For the purpose of the study, research officers who had been working for at least three years with MINT were selected. The variables were operationalised and measured using Herzberg's definitions in the Two-Factor Theory. The items for the variables were derived from instruments used in previous studies conducted by Moses, (1997). Data were collected through personal interviews. Eighty-five respondents were selected for this study. The data collected were analysed using Statistical Package for Social Science (SPSS). Measures of central tendencies and frequencies were employed in the analysis. The reliability coefficients of the variables, using Cronbach' s Alpha, ranged from 0. to 0.97. Demographically, the majority of the respondents were married (98 percent married), males (82 percent), above thirty-five years old (72 percent), had more than seventeen years of formal education (54% held Masters degrees and about 38% held Doctorate degrees), and had been working with MINT for more than 10 years (75%). There were more males than females holding supervisory positions; the ratio was 10:1. In response to the first objective of the study, which was to determine the extrinsic motivation of researchers using the variables of the hygiene factor, the study found that the overall extrinsic motivation of MINT researchers was moderate. The mean score for the overall hygiene factors was 4.6 out of a total of 7.0 with a standard deviation of 1.3. The second objective was to determine the intrinsic motivation of MINT researchers using the variables of the motivator factor, the study found that the overall intrinsic motivation of the researchers was moderate. The mean score for the overall motivator factors was 4.5 out of a total of 7.0 with a standard deviation of 1 .3 .There were eight variables in the hygiene factor. "Interpersonal relations with peers" and "job security" had the highest scores with 5.3 and 5.2 respectively. "MINT policy and administration" had the lowest mean score (3.8) among the eight variables in the hygiene factor. There were six variables in the motivator factor. The highest mean score in the motivator factors was "work itself' and the lowest mean score was "advancement". Overall, the scores of the hygiene and motivator factors were moderate (mean score 4.5). A single item measure on job satisfaction gave a mean score of 4.5 and a standard deviation of 1.2. This value was almost identical with the mean score of the motivator factors. The findings tend to suggest that the overall job motivation of MINT researchers was moderate and it could be implied that the overall job satisfaction was also moderate.